ANSWER
![(d^2y)/(dx^2)=4](https://img.qammunity.org/2023/formulas/mathematics/college/dl7fe5evmx15y9vu9fwtriye71bhgebxi6.png)
Step-by-step explanation
We want to find the second derivative of the function at the given point:
![2-xy-2y=0](https://img.qammunity.org/2023/formulas/mathematics/college/cap4yvk0sl4b22j8y1sjaxdu0n7ycbvun7.png)
First, differentiate the function implicitly:
![0-y-x(dy)/(dx)-2(dy)/(dx)=0](https://img.qammunity.org/2023/formulas/mathematics/college/1urh04ybuiz4wqv1mv5kitvwrlduj0xqkp.png)
Next, differentiate the function implicitly a second time:
![\begin{gathered} -(dy)/(dx)-(dy)/(dx)-x(d^2y)/(dx^2)-2(d^2y)/(dx^2)=0 \\ -2(dy)/(dx)-(x+2)(d^2y)/(dx^2)=0 \\ -(x+2)(d^2y)/(dx^2)=2(dy)/(dx) \\ (d^2y)/(dx^2)=(2)/(-(x+2))(dy)/(dx) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f9wsx1quo21z3gg44m801qj047d6q63w4s.png)
From the first derivative, we have that:
![\begin{gathered} -y-(x+2)(dy)/(dx)=0 \\ -(x+2)(dy)/(dx)=y \\ (dy)/(dx)=(y)/(-(x+2)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zadfepyle1qk5l8qc0oovb2m3dd5xl88f8.png)
Substitute that into the second derivative:
![\begin{gathered} (d^2y)/(dx^2)=(2)/(-(x+2))*(y)/(-(x+2)) \\ (d^2y)/(dx^2)=(2y)/((x+2)^2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8bhwn0fzqz2rzr9f50ahtb7ysv2ssobsih.png)
Now, substitute the values of the point given into the equation and simplify:
![\begin{gathered} (d^2y)/(dx^2)=(2(2))/((-1+2)^2) \\ (d^2y)/(dx^2)=(4)/(1^2) \\ (d^2y)/(dx^2)=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qlj0b9mz6qduf6rzavw712m4wd9r8wjo2d.png)
That is the answer.